O ensino do processo de referenciação no 6º ano do Ensino Fundamental: progressão textual por anáfora - Jankoski, Joslei Aparecida Hank (2021)
This Master thesis reports a research on the approach of nouns in a Portuguese textbook for the 6th year of Elementary School and proposes linguistic analysis activities with the aim to contribute to the teaching of writing. The general objective is to present a didactic unit for addressing the noun as a constitutive element of textual progression by anaphora, and, for achieving this goal, we considered the results of a textbook analysis. In the light of the Reference theory, we followed the perspective that linguistic mechanisms, specifically the nouns, are important clues in written texts. We carried out bibliographic review and textbook analysis, based on which we developed a didactic unit for the 6th year of Elementary School, focusing on the use of nouns for anaphorical reference. Our theoretical framework is based on Antunes (2003; 2007), Koch (2000; 2003; 2005; 2018a; 2018b), Koch and Elias (2018), Marcuschi (2001; 2005a; 2005b; 2008; 2012), among others. We verified that the addressing of nouns proposed in the textbook does not consider the anaphorical processes. For this reason, the didactic proposition presented here focuses on the identification of the referencing process in the development of the students’ linguistic competence not only in the educational context, but also in their broad social context, since it is related to a linguistic phenomenon that indicates the text producer’s viewpoints. We present the noun as an element that constitutes a syntactic structure (the noun phrase) that is largely responsible for text progression. Therefore, we suggest that Reference serves to demonstrate that the noun is an element that convey value judgments in the meanings triggered in the texts.